Effect of Varied NaCl Soaking Treatment on Chemical Composition of Lesser Yam Flour and Its Use in the Production of Gluten-Free Noodles - Ayuningtyas, Laksmi Putri; Putri, Devry Pramesti (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2024)
In order to reduce dependence on wheat flour, it was necessary to use alternative options, such as lesser yam flour. The production of lesser yam flour consisted of soaking yam tubers in NaCl solutions of different concentrations (20% and 25%). This soaking process was necessary for enhancing the physical characteristics of the flour, resulting in reduced mucus and a whiter appearance. The diverse NaCl concentrations during soaking significantly affected chemical composition of lesser yam flour, impacting parameters, including moisture, ash, fat, total protein, reducing sugar, total sugar, glucomannan content, and calories. However, no discernible effect was observed on the crude fiber and carbohydrate content. In comparison to the 25% NaCl, the 20% NaCl had lesser yam flour with lower moisture, ash, protein, total sugar, and reducing sugar content, but higher fat, glucomannan, and calories. The 25% NaCl soaked lesser yam flour was selected for the production of gluten-free dry noodles. Dry noodles were prepared with various proportions of lesser yam flour and mocaf flour, including 0:100 (TG0), 50:50 (TG1), 50:40 (TG2), 70:30 (TG3), 80:20 (TG4), and 90:10 (TG5). An increase in the proportions of lesser yam flour resulted in increased hardness and chewiness, along with decreased springiness and cohesiveness. Therefore, lesser yam could be processed into flour by soaking in NaCl solutions to produce better flour, with the optimal flour composition being 80% lesser yam flour and 20% mocaf flour for gluten-free noodles production. This suggested the potential for further development of lesser yam flour as a raw material for the production of gluten-free noodles.